Hormone Modulation of Toll-Like Receptor 5 in Cultured Human Bladder Epithelial Cells. (May 2017) - Foust-Wright, Caroline E.; Pulliam, Samantha J.; Batalden, Rebecca Posthuma; Berk, Tucker K.; Weinstein, Milena M.; Wakamatsu, May M.; Phillippe, Mark
Aim: The effect of hormone levels on the stimulation of Toll-like receptor 5 (TLR5) in the bladder is unknown. We aimed to study the effect of estradiol and progesterone on TLR5 expression and function in human bladder epithelial cells. Methods: After growing to near confluence, T24 human urinary bladder (HUB) cells were incubated in hormone-free (HF) media for 72 hours. Human urinary bladder cells were then incubated in (1) HF media, (2) estradiol media, (3) progesterone media, or (4) media containing estradiol and progesterone at physiologic concentrations. Following flagellin exposure, cells and media were collected. Toll-like receptor 5 expression and stimulated cytokine release were analyzed using enzyme-linked immunosorbent assays. Results were normalized with cellular protein assays. A TLR5 antagonist was used to confirm that stimulation from flagellin was mediated by TLR5 signaling. Results: Cultured HUB cells express TLR5 protein. Estradiol and progesterone environments suppress TLR5 expression compared to HF environment. The function of TLR5 was measured by interleukin 6 (IL-6) and monocyte chemoattractant protein 1 production after flagellin exposure. Interleukin 6 production was 75% higher in the estradiol than progesterone environment. The progesterone environment produced IL-6 levels twice that observed in HF and combined estrogen–progesterone environments. Interestingly, higher TLR5 expression was associated with lower IL-6 production. Conclusion: Our study demonstrated that TLR5 expression and functional activity as measured by IL-6 are modulated by hormones. The increase in TLR5-associated IL-6 may play a role in increasing the rate of symptomatic urinary tract infection. Likewise, low TLR5 functional activity may dampen the response of the innate immune system, thereby lessening the likelihood of a symptomatic bladder infection.